2011
DOI: 10.1080/02680939.2010.551143
|View full text |Cite
|
Sign up to set email alerts
|

‘I think a lot of it is common sense. …’ Early years students, professionalism and the development of a ‘vocational habitus’

Abstract: This paper reports on research from a small-scale project investigating the vocational training of students in Early Childhood Education and Care (ECEC) in England. We draw on data from interviews with 42 students and five tutors in order to explore the students' understandings of professionalism in early years. In the paper, we discuss first, the then Labour Government's drive to 'professionalise' the workforce and second, critically analyse the concept of professionalism, drawing on sociological literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 23 publications
1
23
0
8
Order By: Relevance
“…Wellgarth promoted vocational habitus in its students during an intense training in the practicalities of childcare and household management. In this way, it reflected contemporary discourse that workingclass girls required such training, a contrast with recent research findings which identified confidence in today's childcare trainees who articulated a view of their work as common sense and not something which, at root, required training (Vincent and Braun 2011). The school sought to build status for its students and to instill a sense of personal and professional responsibility through close control of their lives, during training and subsequently.…”
Section: Concluding Reflections: (Dis)continuities In Past/present Comentioning
confidence: 84%
“…Wellgarth promoted vocational habitus in its students during an intense training in the practicalities of childcare and household management. In this way, it reflected contemporary discourse that workingclass girls required such training, a contrast with recent research findings which identified confidence in today's childcare trainees who articulated a view of their work as common sense and not something which, at root, required training (Vincent and Braun 2011). The school sought to build status for its students and to instill a sense of personal and professional responsibility through close control of their lives, during training and subsequently.…”
Section: Concluding Reflections: (Dis)continuities In Past/present Comentioning
confidence: 84%
“…[13] Profesyonel kimlik kazanım sürecini değerlendirmede, anlamada ve açıklamada habitus kavramının oldukça kullanışlı olduğu belirtilmiştir. [6,[13][14][15]24,25] Profesyonel kimlik veya habitus ise, öncelikle başkalarının ihtiyaçları ile uğraşan özgün bir bilgi birikimine, profesyonel ve bilimsel eylemlere özümsenmiş bir bağlılık sağlar. Bu bağlamda, profesyonel habitus, profesyonel kimlik ve amaçları benimsemek kadar günlük hemşirelik uygulamalarıyla baş etmede gerekli olan yetenek ve yeterliği içermelidir.…”
Section: Bakım Alanında Hemşire Habitusuunclassified
“…At times, the lack of expression is due to a presumed existence of the expertise required, presenting practical wisdom as a set of innate characteristics (McGillivray 2008;Penn 2011). Research from England has demonstrated that prior experiences of caring are often privileged over more theoretical forms of knowledge amongst those undertaking ECEC training (Colley 2006;Skeggs 1997;Vincent and Braun 2011). However, not explicitly expressing experiential knowledge, along with presenting practical wisdom as a set of innate characteristics, renders them invisible in modernist constructs of professionalism that seek knowable features.…”
Section: More Than a Qualificationmentioning
confidence: 99%